Einsatz von Classroom Response Systemen in Übungen - Zangerle, Sebastian; Kuhn, Jochen; Widera, Artur (Progress in science education, 2018)
Background: Classroom response systems (CRS) are an effective way to promote communication between lecturers and students and to improve students' concept understanding. Purpose: The use of CRS in tutorials is still poorly understood. This is why we have studied the added value of using CRS in tutorials in addition to its popular use in lectures. Furthermore, the influence of the CRS on student attitudes towards digital media in teaching and on their confidence in their answers has been examined. Sample/Setting: The sample consists of students attending an experimental physics lecture on the introduction to quantum mechanics at the Bachelor’s level. The sample contains 47 complete datasets and is divided into 25 students in the control group and 22 students in the intervention group. Surveys were conducted at the beginning (pre) and end (post) of the semester. Design Methods: In a quasi-experimental pre / post design, CRS was used in the lecture for all students. The intervention group received additional CRS questions in the tutorials. A questionnaire on attitudes towards digital media in teaching was used, as well as a concept test on wave physics. As part of the concept test, the confidence on the answer was also measured for each question. The analysis of covariance (Ancova) was used to investigate the test results; in the case of non-existent correlations, the analysis of variance (Anova). In the case of the comparison of pre- and post-values, an analysis of (co-) variance with repeated measures was engaged. Results: The use of CRS has a positive effect on students' attitudes towards digital media in teaching (p <0.001, = 0.31). The students with additional CRS use in the tutorials improve their attitude more than their fellow students (p = 0.029, = 0.13). In terms of performance, there were no differences between control and intervention group. Conclusions/Implications for classroom practice and future research: The additional use of CRS in the tutorials beyond the use in the lecture has no influence on the performance of the students. For a better understanding of the dose-effect relationship, the effect of CRS use in tutorials without CRS use in the lecture will be investigated in another study. Hintergrund: Classroom Response Systeme (CRS) sind ein effektives Mittel, um Kommunikation zwischen Dozierenden und Studierenden zu fördern und mit geeigneten Fragen das Konzeptverständnis der Studierenden zu verbessern. Ziel: Der Einsatz von CRS in Übungen ist noch kaum bekannt, weshalb der Mehrwert des CRS-Einsatzes in Übungen zusätzlich zur verbreiteten Verwendung in Vorlesungen untersucht wurde. Weiterhin wurde der Einfluss des CRS-Einsatzes auf die Einstellung der Studierenden gegenüber digitalen Medien in der Lehre und auf ihre Antwortsicherheit überprüft. Stichprobe/Rahmen: Die Stichprobe besteht aus Studierenden, die eine Experimentalphysik Vorlesung zur Einführung in die Quantenmechanik auf Bachelorniveau besuchen. Die Stichprobe enthält 47 vollständige Datensätze und teilt sich in 25 Studierende in der Kontroll- und 22 Studierende in der Interventionsgruppe auf. Erhebungen wurden zu Beginn (Prä) und Ende (Post) des Semesters durchgeführt. Design und Methode: In einem quasi-experimentellem Prä-/Post Design wurde für alle Studierenden in der Vorlesung CRS eingesetzt. Die Interventionsgruppe erhielt zusätzlichen CRS Einsatz in der Übung zur Vorlesung. Es wurde ein Fragebogen zur Einstellung gegenüber digitale Medien in der Lehre eingesetzt, sowie ein Konzepttest zur Wellenphysik. Im Rahmen des Konzepttests wurde zu jeder Frage außerdem noch die Antwortsicherheit abgefragt. Zur Untersuchung der Testergebnisse wurde die Kovarianzanalyse (Ancova) eingesetzt, im Falle nicht vorhandener Korrelationen die Varianzanalyse (Anova), beziehungsweise beim Vergleich von Prä- und Postwerten eine (Ko-)Varianzanalyse mit Messwiederholung. Ergebnisse: Der Einsatz von CRS wirkt sich positive auf die Einstellung der Studierenden gegenüber digitalen Medien in Lehrveranstaltungen aus (p<0,001, =0,31). Die Studierenden mit zusätzlichem CRS Einsatz in den Übungen verbessern ihre Einstellung stärker als ihr Kommilitonen (p=0,029, =0,13). Bezüglich der Leistung gab es keine Unterschiede zwischen Kontroll und Interventionsgruppe. Schlussfolgerungen/Bedeutung für die Lehrpraxis und künftige Forschung: Der zusätzliche CRS-Einsatz in den Übungen über den Einsatz in der Vorlesung hinaus hat keinen Einfluss auf die Leistung der Studierenden. Zum besseren Verständnis der Dosis-Wirkung Beziehung soll in einer weiteren Studie der Effekt des CRS Einsatzes in Übungen ohne CRS Einsatz in der Vorlesung untersucht werden.